hubungan urutan waktu makan buah, sayur, dan kualitas tidur terhadap gula darah dan tekanan darah pasien diabetes melitus tipe 2 - Syaharani, Mutiara Salsabila; Soelistyorini, Dwie; Dwipajati, Dwipajati (UHAMKA PRESS, 2024)
Type 2 diabetes mellitus is the most common type that occurs in society, around 80% of 90% of all diabetes mellitus cases. Modifying the order in which you eat fruit and vegetables can control blood sugar levels. Apart from diet, diabetes sufferers need to pay attention to the quality of their sleep so that blood sugar can be controlled well. Poor sleep quality can affect balance and increase blood pressure. The aim of this study was to determine the relationship between the timing of eating fruit and vegetables and sleep quality on blood sugar and blood pressure in patients with type 2 diabetes mellitus. This study used an analytical observational research design with a cross sectional method with a total of 35 subjects. The statistical analysis test used the Spearman correlation test with a confidence level of 95% (α<0,05). The result of research on the relationship between the order of time to eat fruit and vegetables and blood sugar was p-value=0,27. Then, for the relationship between sleep quality and blood sugar, the result was p-value=0,121, sleep quality with systolic and diastolic blood pressure, the results were p-value=0,561, and p-value= 0,137. There was no significant relationship between the order of time to eat fruit and vegetables on blood sugar and sleep quality on blood sugar and blood pressure.